Lung Cancer Mortality and the Availability of Chest Computerized Tomography: A Longitudinal Nationwide Study. (27th May 2020) - Ponte, Eduardo Vieira; Fanelli, Marcelo Ferretti; Ferreira, Renata Tosoni Rodrigues; Pereira, Juliana Franceschini; Alcadipane, Marília Soares e Silva; de Lima, Valmar Bião; Marchi, Evaldo; dos Santos, Ricardo Sales
Abstract: Lung-cancer screening with chest computerized tomography (CT) is not easy to introduce in low-medium resource countries due to cost issues. We investigated whether the increasing availability of chest CT exams in Brazil, in spite of no lung-cancer screening protocol, was associated with lung-cancer death rate along 10-year follow-up. We performed regressions to estimate the rate ratio between chest CT exams and lung-cancer deaths per 10 5 inhabitants. We stratified data per municipality. Regressions were adjusted for physicians and hospital beds per 10 5 inhabitants and per capita gross domestic product. Increasing availability of chest CT exams predicted decreasing lung-cancer death rate.